Examining parental monitoring as a moderator of the relationship between depressed mood and alcohol use and problems. (June 2018) - Geisner, Irene M.; Trager, Bradley M.; Hultgren, Brittney A.; Larimer, Mary E.; Mallett, Kimberly A.; Turrisi, Rob
Abstract: Background: The comorbidity of depressed mood and college student drinking causes consequences for both the individual and society. Aspects of parenting have been shown to be important for college students' well-being. While some interventions are beginning to address this population, few studies have examined how parental monitoring impacts the relationship between depressed mood, alcohol use, and related consequences. The present study examined whether perceived parental monitoring moderated the relationship between depressed mood and alcohol use and related problems. Methods: Students ( N = 796) completed a survey during the fall semester of their first two years of college at a large, public university assessing drinking and related negative consequences, maternal and paternal monitoring, and depressed mood. Results: Results revealed that maternal and paternal monitoring moderated the relationship between depressed mood and typical weekly drinking, and depressed mood and consequences (i.e., self-perception, self-care, blackouts). Conclusions: Interventions should be tailored to parents based on considerations of both student mental health and alcohol use. Highlights: Importance of parental monitoring understudied in depressed and drinking college students Examine student perception of maternal and paternal monitoring as a moderator Significant moderation between depressed mood and typical weekly drinking and specific consequences